NewSpace systems engineering - Chechile, Ignacio (Springer, 2021)
This book provides a guide to engineering successful and reliable products for the New Space industry. By discussing both the challenges involved in designing technical artefacts, and the challenges of growing an organisation, the book presents a unique approach to the topic. New Space Systems Engineering explores numerous difficulties encountered when designing a space system from scratch on limited budgets, non-existing processes, and great deal of organizational fluidity and emergence. It combines technical topics related to design, such as system requirements, modular architectures, and system integration, with topics related to organizational design, complexity, systems thinking, design thinking and a model based systems engineering. Its integrated approach mean this book will be of interest to researchers, engineers, investors, and early-stage space companies alike. It will help NewSpace founders and professionals develop their technologies and business practices, leading to more robust companies and engineering development.